Feeling safe together vs. longing for touch. Affective, multisensorial contact in inclusive intra-active virtual/physical dance during the COVID-19 pandemic - Oertel, Noora Talvikki (Frontiers in Psychology, 2024)
This article explores how feelings of safety were experienced through inclusive virtual/physical dance in relation to experiences of touch during the COVID-19 pandemic in Finland. These are the steps I took to get the aim: First, I introduce the context through previous studies and an example from the ethnographic material I gained from the inclusive X-Dance festival organized in June 2021 in Finland.Second, I explore how inclusive virtual/physical dance might help us experience feelings of safety through multisensorial experiences of touch related to communality when responding to well-being challenges caused by isolation. Using Laura U. Mark's theory about haptic looking and Karen Barad's term intra-action I discuss possibilities to approach touch as a feeling sense, as affective multisensorial contact, and through relations between different materialities.Third, I contrast these ideas with sensations of longing for the physical touch that virtual/physical dancing evokes. These experiences of longing invite me to reflect on the ambivalence about feelings of safety related to intentions to restore experiences of touch and communality through digitality. I introduce two examples from my interviews with dancers during the pandemic to discuss these ambivalences. I reflect on these interviews through Magdalena Górska's theory about corpo-materiality and corpo-affectivity.I contribute to discussions on feelings of safety by showing that multi-sensorial experiences and antinormative understandings of body and touch enabled by the nonverbal language of dance might help us contribute toward more inclusiveness in society, allowing us to generate holistic experiences of safetyanother critical aim for post-pandemic times.